Pengaruh Terapi Non Farmakologidiabetes Melitus Terhadap Kadar Gula Dalam Darah - Erida Fadila; Sumarmi Sumarmi; Dwi Rahayu; Sutrisno Sutrisno (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: Diabetes Mellitus is called the silent killer, because this disease causes various kinds of complaints and can attack all organs of the body. In Southeast Asia, people with Diabetes Mellitus in Indonesia are ranked 3rd with a prevalence of 11.3%. There are four pillars of diabetes mellitus control including physical activity, diet, pharmacological interventions, and education. Of the four pillars, physical activity is the most effective therapy to prevent blood sugar levels from remaining normal. Physical activities recommended for people with Diabetes Mellitus include walking, cycling, gymnastics and jogging. Purpose: The purpose of this literature review is to determine the effect of non-pharmacological diabetes mellitus therapy on blood sugar levels.Methode: In the search for data sources the article is carried out through the databases Google Scholar, Publish or Perish and Mendeley. Inclusion of study design using Literature Review. Results: The results of the literature review analysis there are 12 journals that ha stated or the alternative hypothesis is accepted. Conclusion: So it can be concluded that there is an influence of non-pharmacological therapy (diet and physical activity) diabetes mellitus on blood sugar levels. The effect of physical activity therapy on a decrease in blood sugar levels by 66.6%. And the effect of dietary therapy on reducing blood sugar levels by 33.3%.